Academic Senate Minutes 2015-04-02 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 3/12/15 – approved. Consent items: Candidates for Graduation and Revision to the Biology BA and BS program – approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Senate input on Hospitality policy revision. Vice President of Associated Students Report. Statewide Senators Report. Posthumous degree request for Francis Lynch approved. Resolution regarding Indiana Religious Freedom Restoration Act amended and approved. EPC Report. FSAC Report. CFA Report. Good of the Order.